Nutrient Removal Of Tropical Bioretention System In Treating Polluted Runoff A Pilot Study - Faudzi, Liyana Mohd (Universiti Sains Malaysia, 2021)
Poor water quality is a common problem nowadays due to the increase in pollution from human activities. Urban runoff comes from residential areas, industrial areas, and agriculture areas containing nitrogen (N) and phosphorus (P), leading to nitrification and eutrophication. In this study, a pilot-scale bioretention system will be used as stormwater Best Management Practices (BMPs) to solve water quality issues in tropical climates. This study included two bioretention pilot sites, a vegetated site with tropical plants, which is Red Hot Hibiscus (Hibiscus rosa-sinensis), Amaryllis (Hippeastrum), Singapore Daisy (Sphagneticola trilobata), Lobster claw (Heliconia rostrata), Alternanthera (Alternanthera cultivar) and a non-vegetated control site. The field study investigated the pollutant removal efficiency between 2 pilot sites in treating polluted runoff and infiltration rate using two methods, single ring infiltration test and Guelph permeameter test. The site uptake from the polluted runoff will be observed by testing the effluent with TSS, TN and TP test for three weeks at 30 mins, 2 hours, 4 hours and 8 hours after the runoff being released. The results showed pollutant removal efficiency for TSS (76%), TN (78%), and TP (71%) for the vegetated site, which is slightly better compared to control site (TSS (75%), TN (76%) and TP (54%)). The infiltration rate at the vegetated site (36-48 cm/hr) shows lower results than the control site (60-108 cm/hr). However, both pilot sites did not meet the requirement by MSMA (5 to 20 cm/hr). This study concluded that the vegetated site has slightly better performance on nutrient removal efficiency, but the infiltration rate did not achieve the MSMA minimum requirement.